(3JfXje hEOGQI GdefTBJ GdSjGMjI hGdafObjI (B/s - (3eGgQ, CMeOs; (3YHO GdSdGe, CHh bMas ((3GdGScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 1999)
(3ebOeGJ CSGSjI,GdhXGFa hGdegGe GdEOGQjI hHfGA egGQGJ GdeOjQjf,EfTGA GdJhcjdGJ GdSjGMjI hGdbhGfjf GdefXeI ddefTBJ GdafObjI hGdSjGMjI aj eUQ,OQGSI MGdI(B((3TQcIl (BR/H (3ddSjGMI(B)s
(3HHdjhZQGajG(B: (3U(B.497s
Keywords: (3GdSjGMI (B- (3GbJUGOjGJs; (3GdafGObs